2017
DOI: 10.1080/00365521.2017.1322138
|View full text |Cite
|
Sign up to set email alerts
|

The Scandinavian baltic pancreatic club (SBPC) database: design, rationale and characterisation of the study cohort

Abstract: The SBPC database provides a mean for future prospective, observational studies of CP in the Northern European continent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…17 Data for the present study were derived from the database as of January 1, 2019, and included data from 11 centers in seven countries in the Scandinavian-Baltic region and Russia (Moscow). The SBPC database is an open multicenter prospective registration of patients with CP with continuously recruitment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Data for the present study were derived from the database as of January 1, 2019, and included data from 11 centers in seven countries in the Scandinavian-Baltic region and Russia (Moscow). The SBPC database is an open multicenter prospective registration of patients with CP with continuously recruitment.…”
Section: Methodsmentioning
confidence: 99%
“…The SBPC database is an open multicenter prospective registration of patients with CP with continuously recruitment. 17 Data for the present study were derived from the database as of January 1, 2019, and included data from 11 centers in seven countries in the Scandinavian-Baltic region and Russia (Moscow). The detailed study protocol and methodology of the SBPC database has previously been published.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent cross-sectional studies, the proportion of patients who reported having pain ranges from 63 to 86%, suggesting that a subset of patients were pain free at the time of assessment 2, 4, 6, 7, 50 . Variability of pain experience was captured in a large multicenter US study of >500 patients – in the year preceding enrollment, 16% patients reported no pain, 53% reported constant and 32% intermittent pain; pain was mild-moderate in 18% and severe 67% patients.…”
Section: Introductionmentioning
confidence: 99%
“…Narcotics was used intermittently by 23% and constantly by 36%. Interestingly, the proportion of patients treated with narcotics is much lower in Europe (stronger opioids used in 31%) 6 .…”
Section: Introductionmentioning
confidence: 99%